A Prospective Study on Treatment of Prosthetic Valve Thrombosis and its Clinical Presentation - Atif Ahmed Khan, Arshad Ali Shah, Syed Dilbahar Ali Shah, Muhammad Aslam, Syed Ahsan Raza, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Objectives: The thrombosis of prosthetic valve is a lethal complication following replacement surgery of the valve. Few patients report with a thrombotic complication because of poor status of anticoagulation with unbalanced checks of INR. This study was conducted to investigate the clinical profile and treatment of thrombosis of prosthetic valve. Study Design: A prospective observational study. Place and Duration: In the Cardiology department of National Institute of Cardiovascular Diseases, Karachi and Nawabshah for one-year duration from January 2021 to December 2021. Methods: 50 patients with prosthetic valve thrombosis diagnosis were included in this study and analyzed. The clinical parameters, demographic profile and one-year follow-up along with in-hospital outcome were analyzed. Results: Out of 50 patients; there were 37(74%) females, aged 11 to 67, with 35.5 ± 7.5 years of mean age. 30 subjects (60%) had a subtherapeutic INR value on admission. Atrial fibrillation occurred in 48% of patients on admission. 78% of patients reported in the first week of onset of symptoms, and the main complaint was dyspnoea, which occurred in 90% of patients. Streptokinase thrombolysis was performed in 46 (92%) patients, and surgery was performed in 4 patients. 42 (84%) patients had Mitral valve thrombosis and 8 (16%) patients had isolated aortic valve thrombosis. 14% was the in-hospital mortality, and no new strokes or major bleeding were observed. Conclusions: Most patients with prosthetic valve thrombosis showed subtherapeutic value of INR and poor patient compliance. Thrombolysis is a beneficial selection for treating patients with thrombosis of prosthetic valve, particularly in Pakistan. Keywords: Thrombolysis, prosthetic valve thrombosis, subtherapeutic.